We might just make it after all : my best friendship with Kate Spade - Arons, Elyce (New York : Gallery Books, 2025)
"A moving portrait of friendship by Elyce Arons as she reflects on her long relationship with Kate Spade, whom she met in college and with whom she cofounded the multi-billion-dollar fashion company as they came of age in 1990s New York. Set against the glitzy and gritty backdrop of downtown New York at the turn of the century, We Might Just Make It After All lovingly and candidly explores the power of a friendship as close as sisterhood, the challenges facing women entrepreneurs in the 1990s, and the timeless elegance of a generation-defining brand."--
Keywords: Arons, Elyce -- Friends and associates; Spade, Kate -- Friends and associates; Fashion designers -- United States; Friendship; Autobiographies; Biographies